Concerning the Training of Philosophers in Our Republic - Lazauskas, Justinas (Problemos, 1968)
The paper presents a short appraisal and review of the training of philosophers in Lithuanian and the dynamics of its qualitative growth in post-war years. It also analyses some of the aspects of the influence of the decisions of the 20th-23rd Congresses of the CPSU to ensure a creative atmosphere in the socio-political and scientific life of the country on the quantitative and qualitative growth of specialists in this particular field. The paper points out the significance of the postgraduate course of the Vilnius V. Kapsukas State University which thanks to the above was further developed. It notes out the importance of the circumstance that the training of qualified specialists in the republic has been closely connected with the development of philosophical thought in other republics and achievements of science on the whole. The paper holds that the prospects of the training of philosophers in the republic are closely linked with the further improvement of the work of the above post-graduate course, with the solution of the problem of setting-up a sector of philosophy at the Academy of Sciences of Lithuanian SSR, with the best use of favourable conditions of the training of young specialists and specialised post-graduate courses in the leading scientific centres of the country as well as with the strengthening of co-ordination between scientific research and the improvement of its quality.